Empowerment of Women Through SHGs in Tirunelveli District,Tamil Nadu - A SWOT Analysis - Subramanian, S. (Prabandhan: Indian Journal of Management, 2010)
The United Nations development Projects (UNDP) has supported a range of activities to eradicate women’s poverty directly in some projects. The projects and programmes focus on micro credit schemes, technical training, organization of self help group on pro-poor social mobilization programmes and long term capacity building programmes. In India, the project has been under the implementation since 1994. The main focus of activity of the SHGs is to generate savings for income generating projects, providing confidence to women, thereby releasing the women from the clutches of moneylenders.